Muscle fibre satellite cells are located at a greater distance from capillaries in patients with COPD compared with healthy controls - Milan W. Betz; Jana De Brandt; Thorben Aussieker; Alejandra P. Monsegue; Dion C.J. Houtvast; Sebastian Gehlert; Lex B. Verdijk; Luc J.C. van Loon; Harry R. Gosker; Ramon J.C. Langen; Wim Derave; Chris Burtin; et al. (ERJ Open Research)
Background COPD is a disease characterised by skeletal muscle dysfunction. A spatial relationship exists between satellite cells and muscle fibre capillaries, which has been suggested to be of major importance for satellite cell function. In the present study we compared the spatial relationship between satellite cells and capillaries in patients with COPD and age-matched healthy older adults. Methods Muscle biopsies were obtained from the vastus lateralis of n=18 patients with COPD (8 female, 10 male; age 66±5 years, mild-to-severe airflow obstruction) and n=18 age-, sex- and body mass index-matched healthy control adults (8 female, 10 male; age 68±5 years). Immunohistochemistry was used to assess type I/II muscle fibre size, distribution, myonuclear content, satellite cell number and fibre capillarisation. In addition, type I/II muscle fibre satellite cell distance to its nearest capillary was assessed. Results The percentage of type II muscle fibres was significantly greater in patients with COPD (62±10%) compared with controls (50±12%, p<0.05). Muscle fibre capillarisation was significantly lower in patients with COPD compared with controls (p<0.05). While satellite cell content was not different between groups, type I and type II satellite cell distance to its nearest capillary was significantly greater in patients with COPD (type I: 21.3±4.8 µm; type II: 26.7±9.3 µm) compared with controls (type I: 16.1±3.5 µm; type II: 22.7±5.8 µm; p<0.05). Conclusion Satellite cells are located at a greater distance from their nearest capillary in patients with COPD compared with age-matched controls. This increased distance could play a role in impaired satellite cell function in patients with COPD.